1969
DOI: 10.12669/pjms.313.7059
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Patient Safety Culture in the Nurses Working in Intensive Care Units

Abstract: Objective:To determine the patient safety culture among nurses working at intensive care units.Methods:This descriptive study was conducted at intensive care units of Health Practice and Research Center of Erciyes University and Kayseri Education and Research Hospital in the city center of Kayseri in Turkey. Three hundred sixteen nurses working at intensive care units at these hospitals were included in the study. Data were collected by using Hospital Survey on Patient Safety Culture (HSOPSC), developed by Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…17 Corroborating, researches conducted in Taiwan, Peru and the United States also presented this dimension as the main strong area of the hospital institutions. [12][13]20 The percentages found were 94%, 80.3% and 81%, respectively, indicating that most subjects feel supportive and respected in their workplaces. 20 Study conducted in Florianópolis (SC), in two Intensive Care Units (ICU), indicated this same dimension as the main one in receiving positive evaluation, but it was not considered a strong area because it received only 62% of positive responses.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…17 Corroborating, researches conducted in Taiwan, Peru and the United States also presented this dimension as the main strong area of the hospital institutions. [12][13]20 The percentages found were 94%, 80.3% and 81%, respectively, indicating that most subjects feel supportive and respected in their workplaces. 20 Study conducted in Florianópolis (SC), in two Intensive Care Units (ICU), indicated this same dimension as the main one in receiving positive evaluation, but it was not considered a strong area because it received only 62% of positive responses.…”
Section: Discussionmentioning
confidence: 96%
“…7,9 It is currently in use in several countries, considered as a valid instrument and assessment of patient safety culture, enabling health care improvement strategies . [8][9][12][13][14] The HSOPSC is made up of 09 sections, arranged from letter A to I, and covers 12 multi-item scaled dimensions, containing a total of 50 items (44 related to specific security culture issues and 6 items related to personal information). Three dimensions are hospital-related, seven work-unit-related dimensions within the hospital, and two outcome variables measured as follows: a) patient safety -measured by a 5-point scale from "excellent" to "failing"; and b) number of reported events -by response categories, such as "none", "1-2 events", "3 to 5 events", "6 to 10 events" and "11 to 20 events".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most positively perceived dimension of safety culture was attributed to “teamwork within department” among both managers and personnel. It has been shown that “teamwork within department” is perceived as the most strength dimension of safety culture among several countries including Saudi Arabia [ 10 ], United Stated America and Turkey [ 16 ]. Teamwork approach allows staffs to work together, share the responsibilities and reduce medical errors.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 12 dimensions of Hospital Survey on Patient Safety Culture, the percentage of positive responses was the highest for "teamwork within units" and lowest for the "non-punitive response to error". 9 In a study from Nepal 64% nurses reported patient safety culture within organization as adequate. Among different dimensions of safety it showed teamwork, organizational learning and feedback as strong areas and management support, non-punitive response and staffing as weak areas 10.…”
Section: Introductionmentioning
confidence: 99%